Anti-collapse ultra-lightweight concrete for traffic engineering and preparation method of anti-collapse ultra-lightweight concrete
By using a combination of modified core-shell structural foam stabilizer and fly ash in ultra-lightweight concrete, the problem of mold collapse in ultra-lightweight concrete during the pouring process is solved, and the stability and resistance of the structure are significantly improved. Impact capability and the advantages of energy saving and emission reduction.
Patent Information
- Application Number
- CN202411292718.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-21
AI Technical Summary
Existing ultralight concrete is prone to collapse during the pouring process, affecting the quality and performance of the structure and increasing construction costs.
A modified foam stabilizer is used, using hydroxypropyl methylcellulose ether and C-S-H nanocrystal core graft copolymer as the core layer, and sulfoaluminate cement clinker as the shell layer to form a modified core-shell structure foam stabilizer. , combined with the ball effect of fly ash, significantly improves the stability and anti-collapse performance of concrete.
It effectively prevents the collapse of concrete during the pouring process, improves the stability and impact resistance of the structure, reduces the amount of cement, and has the advantages of energy saving and emission reduction.
Smart Images

Figure BDA0005045082600000041 
Figure BDA0005045082600000061
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of concrete, and in particular to an anti-collapse ultra-lightweight concrete for traffic engineering and a preparation method thereof. Background Art
[0002] Ultra-lightweight concrete is a special building material with a significant weight-reducing effect. Due to its low density and excellent shrinkage and energy absorption characteristics, it has been widely used in transportation engineering fields such as highway escape lanes and airport runway end arresting systems. Its lightweight characteristics enable it to effectively reduce the deadweight of the structure while maintaining a certain strength, reduce the foundation load, and improve construction efficiency and economy. At the same time, ultra-lightweight concrete can absorb and disperse energy through its own shrinkage characteristics when subjected to impact, thereby enhancing the impact resistance of the structure and improving the safety performance of transportation facilities.
[0003] Although ultra-lightweight concrete has shown significant advantages in many fields, there are still some technical problems that need to be solved in the actual preparation process. Among them, one of the most prominent problems is that it is very easy to collapse. Due to its special proportion and loose and porous structural characteristics, ultra-lightweight concrete is difficult to maintain a stable shape during the pouring process and is prone to collapse. This not only affects the quality and performance of the structure after molding, but also increases the rework rate during the construction process, prolongs the construction period, and thus increases the project cost.
[0004] Therefore, it is urgent to develop a new anti-collapse ultra-lightweight concrete preparation technology to improve its stability and operability and ensure its application effect in actual engineering. Summary of the invention
[0005] In order to overcome the deficiencies in the prior art, a method for preparing an anti-collapse ultra-light concrete for use in traffic engineering is provided, aiming at the problems of collapse and height limitation that have occurred in the casting process of general ultra-light concrete.
[0006] In the first aspect, the present application provides an anti-collapse ultra-lightweight concrete for traffic engineering, which specifically includes the following components in the following amounts: cement 180-220 kg / m 3 , fly ash 70~100kg / m 3 , modified foam stabilizer 2.4~3.7kg / m 3 , Foaming agent 2~2.6kg / m 3 , Water 130~180kg / m 3 , water reducing agent 3~9kg / m 3 Fiber 0.5~2kg / m 3 ; The preparation method of the modified foam stabilizer is as follows: 10 to 30 parts by weight of hydroxypropyl methylcellulose ether and 20 to 40 parts by weight of CSH nanocrystalline cores are mixed and ball-milled at a speed of 200 to 500 rpm in a ball mill for 10 to 300 minutes to obtain a first powder; 30 to 50 parts by weight of the first powder and 70 to 100 parts by weight of sulphoaluminate cement clinker powder are mixed and ball-milled at a speed of 150 to 300 rpm in a ball mill for 10 to 120 minutes to obtain the modified foam stabilizer.
[0007] Preferably, the anti-collapse formwork ultra-lightweight concrete for traffic engineering specifically includes the following components in the following amounts: cement 190-210 kg / m 3 、Fly ash 80~90kg / m 3 , modified foam stabilizer 2.8~3.3kg / m 3 , Foaming agent 2.2~2.4kg / m 3 , Water 140~160kg / m 3 , water reducing agent 5~8kg / m 3 Fiber 1.0~1.5kg / m 3 .
[0008] Preferably, the preparation method of the modified foam stabilizer is: take 15-25 parts by weight of hydroxypropyl methylcellulose ether and 25-35 parts by weight of CSH nanocrystalline cores in a ball mill at a speed of 200-500 rpm and ball mill for 50-150 minutes to obtain a first powder; take 35-45 parts by weight of the first powder and 80-90 parts by weight of sulphoaluminate cement clinker powder in a ball mill at a speed of 150-300 rpm and ball mill for 40-90 minutes to obtain the modified foam stabilizer.
[0009] Preferably, the CSH nanocrystal core is a commercially available product with a solid content of 15% to 30%.
[0010] Preferably, the cement is general-purpose silicate cement, including at least one of silicate cement, ordinary silicate cement, slag silicate cement, pozzolanic silicate cement, and fly ash silicate cement.
[0011] Preferably, the fly ash is fly ash of grade II or above.
[0012] Preferably, the foaming agent is selected from at least one of a rosin-type foaming agent, a surfactant-type foaming agent, a plant-type foaming agent, an animal-type foaming agent, a composite foaming agent, an ammonium salt, hydrogen peroxide or aluminum powder.
[0013] Preferably, the water reducer is at least one of a polycarboxylic acid water reducer, a naphthalene water reducer, an anthracene water reducer, a lignin sulfonate water reducer, an aminosulfonate water reducer, an aliphatic water reducer, and a melamine water reducer.
[0014] Preferably, the fiber is at least one of polypropylene fiber, polyvinyl alcohol fiber and carbon fiber.
[0015] In a second aspect, the present application provides a method for preparing the above-mentioned anti-collapse formwork ultra-lightweight concrete for traffic engineering, which specifically comprises the following steps in sequence: Ingredients: Weigh the corresponding amounts of cement, fly ash, modified foam stabilizer, foaming agent, water, water reducing agent, and fiber; Dry mixing: Put cement, fly ash, modified foam stabilizer and fiber into a mixer, mix and stir for 60 to 120 seconds to obtain dry mixed materials; Slurrying: dispersing the water reducer in 1 / 2 amount of water and injecting the mixture into the dry mixed material, and continuing stirring for 60 to 120 seconds to obtain slurry; Preparation of anti-collapse ultra-lightweight concrete: stir the remaining water and the foaming agent at a rotation speed of 1000-3000 rpm for 10-60 seconds, add the stirred foaming agent into the slurry and stir at a rotation speed of 10-600 rpm for 60-180 seconds to obtain the anti-collapse ultra-lightweight concrete.
[0016] In summary, the technical solution of this application has the following effects: In the modified core-shell structure foam stabilizer prepared from hydroxypropyl methylcellulose ether, CSH nanocrystalline core and sulphoaluminate cement clinker, the core layer is a graft copolymer of hydroxypropyl methylcellulose ether and CSH nanocrystalline core, and the shell layer is sulphoaluminate cement clinker. When the modified foam stabilizer comes into contact with water, it starts to hydrate from the shell to the core, and the ions are dissolved out in sequence. The sulphoaluminate cement clinker in the shell layer reacts rapidly with water first, and the hydration products form a matrix skeleton structure, thereby improving the matrix stability; when the shell layer reacts completely, the foam stabilizer modified by the CSH nanocrystalline core in the core layer is dissolved, and its excellent film-forming and bonding properties improve the toughness of the bubble film and improve the stability of the foam. The addition of the CSH nanocrystalline core increases the number of nucleation sites, greatly reduces the nucleation barrier of the cement product, promotes the closure and uniform distribution of the pores inside the concrete, reduces the number of connected pores, improves the mechanical properties of the matrix, and effectively prevents the collapse of the mold.
[0017] The fly ash of the present application has an excellent ball effect itself. Coupling it with a modified core-shell structure foam stabilizer can significantly improve the collapse of ultra-light concrete. Using fly ash as an auxiliary cementitious component also reduces the amount of cement used, which is beneficial to energy conservation and emission reduction.
[0018] The main performance parameters of the ultra-lightweight concrete prepared in this application are: Bulk density: 180-200 kg / m 3The crush strength is 0.3-0.35MPa, and its crush strength remains basically stable after 60 days, ensuring the safety of equipment and personnel in transportation engineering fields such as highway escape lanes and airport runway end arresting systems.
[0019] The ultra-lightweight concrete prepared in the present application can still maintain the mold from collapsing when the one-time pouring height reaches 0.5 to 2 meters.
[0020] The preparation process of the present application is simple and easy to operate. The ultra-lightweight concrete is easy to produce and can more effectively prevent the mold collapse after pouring. There is no need for rework in the later stage and the application is highly practical. DETAILED DESCRIPTION
[0021] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in the present application.
[0022] The raw material hydroxypropyl methylcellulose ether used in this application comes from Shandong Feicheng Yutian Chemical Co., Ltd.; CSH nanocrystalline core comes from Jiangsu Subote New Materials Co., Ltd.; sulphoaluminate cement clinker powder comes from Xingtai Zhonglian Cement Co., Ltd.; Class II fly ash comes from Huaneng Dalian Power Plant; rosin-type foaming agent comes from Jinan Junde Trading Co., Ltd.; polycarboxylic acid water reducer comes from Jiangsu Subote New Materials Co., Ltd.; polyvinyl alcohol fiber comes from Anhui Wanwei Group Co., Ltd.; the remaining raw materials can be obtained through ordinary commercial purchase. Example
[0023] Examples 1-5 Examples 1-5 respectively provide an anti-collapse ultra-lightweight concrete for traffic engineering and a preparation method thereof.
[0024] The difference between the above embodiments is that the dosage of each component in the anti-collapse formwork ultra-lightweight concrete for traffic engineering is different, as shown in Table 1.
[0025] The method for preparing the anti-collapse formwork ultra-lightweight concrete for traffic engineering in the above embodiment is as follows: Preparation of modified foam stabilizer: 20 g of hydroxypropyl methylcellulose ether and 30 g of CSH nanocrystal core are mixed and ball-milled at 350 rpm in a ball mill for 100 min to obtain a first powder; 40 g of the first powder and 85 g of sulphoaluminate cement clinker powder are mixed and ball-milled at 200 rpm in a ball mill for 60 min to obtain a modified foam stabilizer.
[0026] Ingredients: According to 15L of finished concrete and the dosage in Table 1, weigh the corresponding weights of ordinary Portland cement, Class II fly ash, modified foam stabilizer, rosin-type foaming agent, water, polycarboxylate water reducer, and polyvinyl alcohol fiber; Dry mixing: put cement, fly ash, modified foam stabilizer and fiber into a mixer, mix and stir for 1.5 minutes to obtain dry mixed materials; Slurry preparation: disperse the water reducer in 1 / 2 amount of water and inject it into the dry mixed material, continue stirring for 90 seconds to obtain slurry; Preparation of anti-collapse ultra-lightweight concrete: stir the remaining water and the foaming agent at a rotation speed of 2000 rpm for 40 seconds, add the stirred foaming agent into the slurry and stir at a rotation speed of 350 rpm for 120 seconds to obtain the anti-collapse ultra-lightweight concrete.
[0027] Table 1 Amount of each component in the anti-collapse formwork ultra-lightweight concrete for traffic engineering in Examples 1-5 Embodiment 6-9 Examples 6-9 respectively provide an anti-collapse ultra-lightweight concrete for traffic engineering and a preparation method thereof.
[0028] The difference between the above embodiment and embodiment 2 is that the preparation method of the modified foam stabilizer is different, as shown below.
[0029] In Example 6: The preparation method of the modified foam stabilizer is as follows: 10 g of hydroxypropyl methylcellulose ether and 40 g of CSH nanocrystal core are mixed and ball-milled at 350 rpm in a ball mill for 100 min to obtain a first powder; 30 g of the first powder and 100 g of sulphoaluminate cement clinker powder are mixed and ball-milled at 200 rpm in a ball mill for 60 min to obtain a modified foam stabilizer.
[0030] In Example 7: The preparation method of the modified foam stabilizer is as follows: 30 g of hydroxypropyl methylcellulose ether and 20 g of CSH nanocrystal core are mixed and ball-milled at 350 rpm in a ball mill for 100 min to obtain a first powder; 50 g of the first powder and 70 g of sulphoaluminate cement clinker powder are mixed and ball-milled at 200 rpm in a ball mill for 60 min to obtain a modified foam stabilizer.
[0031] In Example 8: The preparation method of the modified foam stabilizer is as follows: 15 g of hydroxypropyl methylcellulose ether and 35 g of CSH nanocrystal core are mixed and ball-milled at 350 rpm in a ball mill for 100 min to obtain a first powder; 35 g of the first powder and 90 g of sulphoaluminate cement clinker powder are mixed and ball-milled at 200 rpm in a ball mill for 60 min to obtain a modified foam stabilizer.
[0032] In Example 9: The preparation method of the modified foam stabilizer is as follows: 25 g of hydroxypropyl methylcellulose ether and 25 g of CSH nanocrystal core are mixed and ball-milled at 350 rpm in a ball mill for 100 min to obtain a first powder; 45 g of the first powder and 80 g of sulphoaluminate cement clinker powder are mixed and ball-milled at 200 rpm in a ball mill for 60 min to obtain a modified foam stabilizer.
[0033] The remaining process parameters in the above embodiment are the same as those in Embodiment 2.
[0034] Comparative Example Comparative Examples 1-3 Comparative Examples 1-3 respectively provide an anti-collapse ultra-lightweight concrete for traffic engineering and a preparation method thereof.
[0035] The difference between the comparative example and Example 2 is that the dosage of each component in the anti-collapse formwork ultra-lightweight concrete for traffic engineering is different, as shown in Table 1.
[0036] The remaining process parameters in the above embodiment are the same as those in Embodiment 2.
[0037] Comparative Example 4 Comparative Example 4 provides an anti-collapse ultra-lightweight concrete for traffic engineering and a preparation method thereof.
[0038] The difference between Comparative Example 4 and Example 2 is that the amounts of the components in the anti-collapse formwork ultra-lightweight concrete for traffic engineering are different, as shown in Table 1.
[0039] In Comparative Example 4: The preparation method of the modified foam stabilizer is as follows: 35 g of hydroxypropyl methylcellulose ether and 15 g of CSH nanocrystal core are mixed and ball-milled at 350 rpm in a ball mill for 100 min to obtain a first powder; 25 g of the first powder and 105 g of sulphoaluminate cement clinker powder are mixed and ball-milled at 200 rpm in a ball mill for 60 min to obtain a modified foam stabilizer.
[0040] The remaining process parameters in Comparative Example 4 are the same as those in Example 2.
[0041] Comparative Example 5 Comparative Example 5 provides an anti-collapse ultra-lightweight concrete for traffic engineering and a preparation method thereof.
[0042] The difference between Comparative Example 5 and Example 2 is that the preparation method of concrete is different, as shown below.
[0043] Ingredients: weigh corresponding grams of ordinary Portland cement, grade II fly ash, modified foam stabilizer, rosin-type foaming agent, water, polycarboxylate water reducer, and polyvinyl alcohol fiber respectively; Dry mixing: put cement, fly ash, modified foam stabilizer, fiber, water reducing agent and foaming agent into a mixer, mix and stir for 1.5 minutes to obtain dry mixed materials; Preparation of anti-collapse ultra-lightweight concrete: Add water to the dry mixed material and stir at a speed of 350 rpm for 120 seconds to obtain anti-collapse ultra-lightweight concrete.
[0044] The remaining process parameters in Comparative Example 5 are the same as those in Example 2.
[0045] Performance testing The bulk density and collapse strength of the concrete prepared in the examples and comparative examples were tested; the collapse strength of the concrete was tested after the concrete was cured for 3 days and 60 days.
[0046] Test results: as shown in Table 2.
[0047] Table 2 Performance test results of concrete in the examples and comparative examples Combined with Table 2, by comparing the performance test results of the concrete in the embodiment and the comparative example, it can be seen that the main performance parameters of the ultra-lightweight concrete prepared by the technical solution provided by the present application are: bulk density is 180-200 kg / m 3 The crush strength is 0.3-0.35MPa, and its crush strength remains basically stable after 60 days, ensuring the safety of equipment and personnel in transportation engineering fields such as highway escape lanes and airport runway end arresting systems.
[0048] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. An anti-collapse formwork ultra-lightweight concrete for traffic engineering, characterized in that: Specifically, it includes the following components: cement 180~220kg / m 3 、Fly ash 70~100kg / m 3 , modified foam stabilizer 2.4~3.7kg / m 3 , Foaming agent 2~2.6kg / m 3 , Water 130~180kg / m 3 , water reducing agent 3~9kg / m 3 Fiber 0.5~2kg / m 3 ; The preparation method of the modified foam stabilizer is as follows: 10 to 30 parts by weight of hydroxypropyl methylcellulose ether and 20 to 40 parts by weight of CSH nanocrystalline cores are mixed and ball-milled at a speed of 200 to 500 rpm in a ball mill for 10 to 300 minutes to obtain a first powder; 30 to 50 parts by weight of the first powder and 70 to 100 parts by weight of sulphoaluminate cement clinker powder are mixed and ball-milled at a speed of 150 to 300 rpm in a ball mill for 10 to 120 minutes to obtain the modified foam stabilizer.
2. The anti-collapse formwork ultra-lightweight concrete for traffic engineering according to claim 1, characterized in that: Specifically, it includes the following components: cement 190~210kg / m 3 、Fly ash 80~90kg / m 3 , modified foam stabilizer 2.8~3.3kg / m 3 , Foaming agent 2.2~2.4kg / m 3 , Water 140~160kg / m 3 , water reducing agent 5~8kg / m 3 Fiber 1.0~1.5kg / m 3 .
3. The anti-collapse formwork ultra-lightweight concrete for traffic engineering according to claim 1, characterized in that: The preparation method of the modified foam stabilizer is as follows: 15-25 parts by weight of hydroxypropyl methylcellulose ether and 25-35 parts by weight of CSH nanocrystalline cores are mixed and ball-milled at a speed of 200-500 rpm in a ball mill for 50-150 minutes to obtain a first powder; 35-45 parts by weight of the first powder and 80-90 parts by weight of sulphoaluminate cement clinker powder are mixed and ball-milled at a speed of 150-300 rpm in a ball mill for 40-90 minutes to obtain the modified foam stabilizer.
4. The anti-collapse formwork ultra-lightweight concrete for traffic engineering according to claim 1, characterized in that: The CSH nanocrystalline core is a commercially available product with a solid content of 15% to 30%.
5. The anti-collapse formwork ultra-lightweight concrete for traffic engineering according to claim 1, characterized in that: The cement is selected from general-purpose silicate cement, including at least one of silicate cement, ordinary silicate cement, slag silicate cement, pozzolanic silicate cement, and fly ash silicate cement.
6. The anti-collapse formwork ultra-lightweight concrete for traffic engineering according to claim 1, characterized in that: The fly ash is selected from fly ash of grade II or above.
7. The anti-collapse formwork ultra-lightweight concrete for traffic engineering according to claim 1, characterized in that: The foaming agent is selected from at least one of rosin-type foaming agents, surfactant-type foaming agents, plant-type foaming agents, animal-type foaming agents, composite foaming agents, ammonium salts, hydrogen peroxide or aluminum powder.
8. The anti-collapse formwork ultra-lightweight concrete for traffic engineering according to claim 1, characterized in that: The water reducer is selected from at least one of polycarboxylic acid water reducer, naphthalene water reducer, anthracene water reducer, lignin sulfonate water reducer, aminosulfonate water reducer, aliphatic water reducer and melamine water reducer.
9. The anti-collapse formwork ultra-lightweight concrete for traffic engineering according to claim 1, characterized in that: The fiber is selected from at least one of polypropylene fiber, polyvinyl alcohol fiber and carbon fiber.
10. The method for preparing the anti-collapse formwork ultra-lightweight concrete for traffic engineering according to any one of claims 1 to 9, characterized in that: Specifically, the following steps are performed in sequence: Ingredients: Weigh the corresponding amounts of cement, fly ash, modified foam stabilizer, foaming agent, water, water reducing agent, and fiber; Dry mixing: Put cement, fly ash, modified foam stabilizer and fiber into a mixer, mix and stir for 60-120 seconds to obtain dry mixed materials; Pulping: Disperse the water reducer in 1 / 2 amount of water and inject it into the dry mixed material, continue stirring for 60-120 seconds to obtain slurry; Preparation of anti-collapse ultra-lightweight concrete: stir the remaining water and the foaming agent at a speed of 1000-3000 rpm for 10-60 seconds, add the stirred foaming agent into the slurry and stir at a speed of 10-600 rpm for 60-180 seconds to obtain the anti-collapse ultra-lightweight concrete.